HFA-PEFF score as a prognostic factor in patients with liver cirrhosis. (3rd October 2022) - Dimitroglou, Y; Vasilieva, L; Patsourakos, D; Tsartsalis, D; Koukos, M; Kalompatsou, A; Valatsou, A; Christofi, A; Zisimos, K; Leontsinis, I; Nitsa, A; Alexopoulou, A; et al.
Abstract: Introduction: Cardiovascular complications of liver cirrhosis which are frequently referred to as cirrhotic cardiomyopathy (CCM), include high cardiac output, reduced afterload and diastolic dysfunction. However, there are only scarce or even conflicting data about the prognostic significance of CCM. HFA-PEFF score is a diagnostic score for heart failure with preserved ejection fraction (HFpEF), which has prognostic value in HFpEF patients. It has functional, morphological and biomarker domains and the score may vary from 0 to 6. Score of 5 or 6 is diagnostic of HFpEF in symptomatic patients. No study has calculated HFA-PEFF score in cirrhotic patients to date. Purpose: The purpose of this prospective study was to calculate HFA-PEFF score in cirrhotic patients, correlate it with disease severity and determine its prognostic significance. Methods: A total number of 92 consecutive cirrhotic outpatients were prospectively examined and 72 fulfilled the inclusion criteria. Patients older than 75 years old or patients with ejection fraction (LVEF) <50%, coronary artery disease, moderate or severe valvular heart disease, atrial fibrillation, ongoing alcohol consumption, hepatocellular carcinoma and poor acoustic window were excluded. In all patients a thorough echocardiographic examination was performed, BNP or NT-pro-BNP levels were measured and subsequently HFA-PEFF score was calculated. MELD score was used to define the severity of cirrhosis. The median follow-up was 20 months and the study end-point was defined as the composite of all-cause death. Results: Mean age was 58.5±8.3 years, 52 (72.2%) were males, median Meld score was 12.9 (8.5–16.3) and mean LVEF was 61.1±5.4%. HFA-PEFF score was 5 or 6 in 38 (52.8%), 2–4 in 27 (37.5%) and 0 or 1 in 9 (9.7%) patients. According to Spearman's coefficient analysis, HFA-PEFF score was correlated with MELD score (rho=0.566, p<0.001), but not with age, systolic blood pressure (SBP) and heart rate. The survival analysis stratified by the HFA-PEFF score [low, score 0–4 (N=34) vs. high, score 5–6 (N=38)] indicated that the HFA-PEFF score successfully predicted all cause two-year survival (log-rank test p<0.001). According to the Cox-regression proportion hazard models HFA-PEFF score as a continuous variable correlated with six-month, one year and two year survival. When HFA-PEFF was treated as a categorical variable, hazard models were significant for the one and two-year survival. The multivatiate COX regression survival analysis showed that the increased HFA-PEFF score (low: score 0–4, N=34 vs high: score 5–6, N=38) was significantly associated with decreased two-year survival when patient age, gender and MELD score are taken into account [HR=3.659 (1.068–12.536), p=0.039]. Conclusions: HFA-PEFF score is high among patients with liver cirrhosis, especially those with increased disease severity. HFA-PEFF score is associated with survival even when adjusting for the severity of the cirrhosis. Funding Acknowledgement: Type of funding sources: None.